PO.5.102 Pharmacokinetic modelling of belimumab in patients with lupus nephritis: intravenous and subcutaneous loading dose regimen justification. (27th September 2022) - Parodis, I; Liefaard, L; Green, Y; Gilbride, JA; Henning, C; Levy, RA; Dimelow, R
Abstract : Purpose: Intravenous (IV) belimumab (BEL) is approved for lupus nephritis (LN) based on the BLISS-LN study (GSK Study BEL114054, NCT01639339 ), which showed that BEL 10 mg/kg IV every 4 weeks with loading to Week 4 (administered as an additional 10 mg/kg dose at Week 2) was efficacious. 1, 2 Exposure-response analyses showed that proteinuria-based dose adjustment was not required, 3 supporting the approval of this dose for LN. The same dose is approved for extra-renal systemic lupus erythematosus (SLE).2 Unlike the IV dose, the approved subcutaneous (SC) regimen in extra-renal SLE (200 mg once weekly [QW]) does not include loading and takes up to 12 weeks for exposure to reach steady state (SS). 4 SC BEL has not been studied in LN, and although the absence of SC loading does not impact efficacy in SLE, it is unknown whether this also applies to active LN, where proteinuria is higher. Therefore, pharmacokinetic (PK) simulations were used to evaluate SC loading dose regimens in patients (pts) with LN, aiming to match the early exposure observed with BEL IV and to inform the most appropriate time to switch from IV to SC dosing during initial treatment. Methods: A post hoc population PK model for IV dosing in pts with LN was developed from the BLISS-LN dataset. The model was extended to include SC dosing, considering the absorption parameters from the model previously developed for SC dosing in pts with SLE.4 The model was used to simulate BEL exposure for IV and SC dosing in pts with LN. The SC regimen was evaluated with and without loading ( Table 1 ). PK simulations were also used to evaluate BEL exposure for an IV to SC switch after the Week 2 IV loading dose. Each dosing regimen simulated BEL PK in 1000 virtual pts. Results: Average BEL exposure over the first 12 (Cavg[0–12]) and 24 weeks are shown in Figure 1 . SC dosing without loading resulted in lower BEL exposure than IV dosing (Cavg[0–12]: 56.7 µg/ml vs 88.8 µg/ml, respectively). Adding a 4-week loading period (400 mg QW to Day 21) to SC dosing raised BEL exposure for Week 0–12 to average levels similar to those of IV dosing (Cavg[0–12]: 78.3 µg/ml vs 88.8 µg/ml, respectively). Switching from IV to SC at Weeks 3 or 4 (i.e. after the Week 2 IV loading) was shown to yield similar average exposures over the first 12 and 24 weeks compared with remaining on IV. After 24 weeks, when proteinuria levels had decreased in response to treatment and BEL PK was close to SS, the IV and SC regimens predicted similar BEL exposures ( Figure 1 and 2 ). Conclusions: PK simulations predicted that the SC dose with 4-week loading (400 mg QW to Day 21) would achieve an average BEL exposure similar to that of the IV regimen. Overall, the results from BLISS-LN and PK simulations support the approval of the IV dose and SC dosing with loading, with no additional dose adjustments required for proteinuria levels. References: Furie R, et al . N Engl J Med. 2020;383 :1117–28. GlaxoSmithKline. Benlysta US prescribing information. 2021. European Medicines Agency. Benlysta (belimumab): Assessment report 2021. Struemper H, et al . Clin Pharmacokinet. 2018;57 :717–28. Funding: GSK.